ANALISIS DAMPAK DAN FAKTOR ADDENDUM PEKERJAAN PELEBARAN JEMBATAN TAJI (NGRAHO – TAJI 19 RUAS NO.56 KECAMATAN NGRAHO BOJONEGORO) - Ayu Kurnia (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2023)
The Taji bridge widening project (Ngraho – Taji 19 Section No. 56, Ngraho Bojonegoro District) experienced an addendum due to unfavorable weather at the location, which resulted in landslides. So the design underwent changes, which was originally planned to be 6.9 meters wide and 20 meters long, in the addendum it became 6.1 meters wide and 20 meters long. In the process, there has also been an increase, from 120 (one hundred and twenty) calendar days to 134 (one hundred and thirty) calendar days. So research was carried out with the aim of looking for factors that influence the occurrence of addendums on work projects, identifying any impacts that occur due to addendums on work projects, and also looking for solutions to overcome the existence of addendums on work projects. Then interviews were conducted with internal parties to obtain more detailed information, and questionnaires were also distributed to the agencies participating in the work project as many as 32 respondents. The questionnaire focused on looking for factors that cause addendums, the impact of addendums, and solutions for addendums. Validity and reliability testing was also carried out, so that the results of the questionnaire distributed were proven to be valid using the Pearson Product Moment method and Cronbach's Alpha reliability test, as well as ranking variable indicators using the Relative Importance Index (IKR). Then the results were obtained that the questionnaire was valid and had a very high level of reliability. For the questionnaire ranking results, it was found that the factor that frequently occurs is construction with a mean value of 3.01, then the most influential impact is time with a mean value of 3.30 and the most appropriate solution in the aspect of time with a mean value of 3.93. So that service providers can prioritize solutions in terms of the time aspect, because the mean value is the highest